Program Pengajaran Bahasa Arab bagi Masyarakat di Kelurahan Tahoa Kabupaten Kolaka - Azwar Azwar; Chamdar Nur (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The purpose of the Real Work Lecture (KKN) STIBA Makassar Batch IV is as a form of community service which is a pillar of the tridarma of universities, especially in the teaching of Arabic as the main program. The method of implementation of the service program begins by mapping the problems and needs of the community using SOAR analysis. After the analysis is done, a work program is prepared that is appropriate and needed by the community. After the analysis is done, it is prepared a work program that is appropriate and needed by the community. Successful work programs include: Simā'an Hafalan Santri, Social Service, Silaturahmi, Tajwid Science Teaching and Arabic Language Teaching as the main program of KKN STIBA Makassar Students. All these programs managed to run well and have shown results that are in accordance with the objectives of the KKN that have been proclaimed, namely the development of Islamic knowledge, increasing the capacity and reading skills of the Qur'an and the Arabic language of the community.